Preliminary morphological and molecular work on mudskippers from Asajaya, Sibu and Telaga Air, Sarawak - Nur Hazwanie Izyan, Binti Mohd Nizam (Universiti Malaysia Sarawak (UNIMAS), 2012)
Mudskippers (Gobiidae: Oxudercinae) live in the intertidal habitat of the mudflats and in the mangrove ecosystem. This study is designed to document morphological details of mudskipper samples from Asajaya, Sibu and Telaga Air, Sarawak. Limited molecular data on mudskipper in Malaysia had been found; therefore this study also aimed to carry out preliminary molecular studies of mudskipper samples from Asajaya, Sibu and Telaga Air, Sarawak. Live samples of mudskippers' samples from Asajaya, Sibu and Telaga Air, Sarawak were collected which then transported immediately to Faculty of Resource Science and Technology (FRST) laboratory and preserved in -20°C freezer. Based on selected morphological characters and meristic counts, there were 4 species of mudskippers found in Asajaya identified as Periophthalmus variabilis, Periophthalmodon septemradiatus, Boleophthalmus pectin irostris and Boleophthalmus boddarti; mudskippers from Sibu were identified as Periophthalmodon septemradiatus; and 3 species of mudskippers found in Telaga Air were identified as Boleophthalmus boddarti, Boleophthalmus pectinirostris and Periophthalmodon schlosseri. For laboratory work, total genomic DNA was extracted from muscle tissues using modified (CT AB) method. Cytochrome oxidase subunit I (COl) gene of Boleophthalmus boddarti of size 500bp had been successfully amplified; however DNA sequencing gave unsatisfactory result.